Performance simulation and testing of capacitive micro-machined ultrasonic transducer. Issue 4 (15th July 2019) - Zhang, Rui; Zhao, Lei; Xie, Dan; Song, Jinlong; Zhang, Wendong; Pan, Lihu; Zhang, Yanhua
Abstract : Purpose: This study aims to simulate and test the performance of a transmitting and receiving capacitive micro-machined ultrasonic transducer (CMUT). Aimed at detecting demand of the CMUT, a matched integrated adjustment circuit was designed through analyzing processing methods of transducer's weak echo signal. Design/methodology/approach: Based on the analysis of CMUT array structure and work principle, the CMUT units are designed and the dynamic performance analysis of SIMULINK is given according to the demand of underwater detecting. A transceiver isolation circuit is used to make transmission mode and receiving mode separate. A detection circuit is designed based on the transimpedance amplifier to achieve extraction of high-frequency and weak signal. Findings: Through experimentation, the effectiveness of the CMUT performance simulation and the transceiver integrated adjustment circuit were verified. In addition, the test showed that CMUT with 400 kHz frequency has wider bandwidth and better dynamic characteristics than other similar transducers. Originality/value: This paper provides a theoretical basis and design reference for the development and application of CMUT technology.